Upper elementary math teachers self-reported instructional practices and justifications of teaching word problems - El-Baba, Ilham Yahya (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2011)
The study examined the self-reported instructional practices followed by Lebanese school math teachers when teaching word problems among upper elementary grade level students in both public and private schools. Chapman s framework of the teaching of word problems, inspired by Bruner s two modes of knowing: the paradigmatic mode and the narrative mode formed the basis for analyzing collected data. Sixty nine teachers were selected from 21 schools located in Sidon, a city in South Lebanon, to fill out a questionnaire. A sample of 12 teachers was selected to participate in a semi-structured interview. The findings highlighted teachers self-reported practices in relation to Chapman s paradigmatic and narrative teaching approaches and explored their justifications for teaching word problems. The study has implications for the professional development of mathematics teachers in the area of word problems and consequently for students performance on solving these types of problems.
: Mémoire
Keywords: Cycle primaire L enseignement du Maths; Elementary Education Math education; Performance professionnel; Professional performance